Nitrogen-Rich and Fire-Resistant Carbon Aerogels for the Removal of Oil Contaminants from Water - Yang, Yu; Tong, Zhen; Ngai, To; Wang, Chaoyang (ACS applied materials & interfaces, 2014)
Effective removal of crude oils, petroleum products, organic solvents, and dyes from water is of significance in oceanography, environmental protection, and industrial production. Various techniques including physical and chemical absorption have been developed, but they suffer from problems such as low separation selectivity, a complicated and lengthy process, as well as high costs for reagents and devices. We present here a new material, termed nitrogen-rich carbon aerogels (NRC aerogels,) with highly porous structure and nitrogen-rich surfaces, exhibiting highly efficient separation of specific substances such as oils and organic pollutants. More importantly, we demonstrate that the fabricated NRC aerogels can also collect micrometer-sized oil droplets from an oil-water mixture with high efficiency that is well beyond what can be achieved by most existing separation methods, but is extremely important in practical marine oil-spill recovery because a certain amount of oils often shears into many micrometer-sized oil droplets by the sea wave, resulting in enormous potential destruction to marine ecosystem if not properly collected. Furthermore, our fabricated material can be used like a recyclable container for oils and chemicals cleanup because the oil/chemical-absorbed NRC aerogels can be readily cleaned for reuse by direct combustion in air because of their excellent hydrophobicity and fire-resistant property. We demonstrate that they keep 61.2% absorption capacity even after 100 absorption/combustion cycles, which thus has the highest recyclability of the reported carbon aerogels. All these features make these fabricated NRC aerogels suitable for a wide range of applications in water purification and treatment.